Modeling Multifrequency Pol-InSAR Data From the Percolation Zone of the Greenland Ice Sheet - Fischer, Georg; Papathanassiou, Konstantinos P.; Hajnsek, Irena (IEEE Transactions on Geoscience and Remote Sensing, 2019)
ISSN:0196-2892 ISSN:1558-0644